2015
DOI: 10.18517/ijaseit.5.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nutraceutical Product

Abstract: The aim of this study was to discuss the development of nutraceutical product which includes the current market trends, challenges, and exploitation of natural resources through various processing. Wet granulation and dry granulation techniques were adopted for such processes. Wet granulation covers high shear mixing granulation, fluidized bed granulation, and twin screw granulation. Dry granulation covers roll compaction and uniaxial die compaction. These techniques were compared and reviewed in terms of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In addition to the above finding, the current study suggests that the chitosan SETs supports the initial attachment, spreading and proliferation of HFSCs in vitro. This phenomenon is likely due to close binding between the positively charged chitosan and the negatively charged cells [21]. Other reports have demonstrated that both fibroblasts and keratinocytes attached to and proliferated well on a chitosan-based scaffold [33], [34].…”
Section: Attachment and Proliferation Of Hfscs On Chitosan Setsmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to the above finding, the current study suggests that the chitosan SETs supports the initial attachment, spreading and proliferation of HFSCs in vitro. This phenomenon is likely due to close binding between the positively charged chitosan and the negatively charged cells [21]. Other reports have demonstrated that both fibroblasts and keratinocytes attached to and proliferated well on a chitosan-based scaffold [33], [34].…”
Section: Attachment and Proliferation Of Hfscs On Chitosan Setsmentioning
confidence: 85%
“…Natural polymeric scaffolds, including collagen-, hydrogel-or chitosan-based scaffolds, have been the focus, as they have favourable biomechanical properties, significant nutraceutical properties [21], [22] and are both biodegradable and biocompatible [10]. In contrast, synthetic materials are found to generate acidic products that cause onsite inflammation, which is harmful to the surrounding tissue [23].…”
Section: K Microstructure Of Chitosan Setsmentioning
confidence: 99%
“…Good compressibility of a dosage form is needed to encourage drug development in industrial pharmacy. Optimization of particle size and density generally leads to a corresponding improvement in compressibility (Yusof et al, 2015) . In a study by Sun et al (2019) the formulation of ca eine (CAF) and methyl gallate in a cocrystal form provides increased compressibility to CAF tablets.…”
Section: Compressibility and Palatabilitymentioning
confidence: 99%
“…Nutraceuticals are food or parts of food that provide medical or health benefits, including the prevention and treatment of diseases. 16,17 A few researchers have investigated plants like the Centella asiatica, Ginkgo biloba, and Polygonum minus for their neuroprotective properties in older people, with neuropsychological tests as outcomes. 11,13,18 To determine the potential ability of nutraceuticals to prevent neurodegenerative diseases, it is necessary to implement a different approach for the assessment of cognitive functions, that is, by determining the level of activation of the brain, this this case, with a functional MRI (fMRI) .…”
mentioning
confidence: 99%